Flood-Irrigated Corn Cost-Return Budget in western Kansas - Dumler, Troy J.; Thompson, Curtis R.; Stockton, Roger (My University, 2003)
This publication projects a budget that reflects expected income and costs based on flood-irrigated corn production in western Kansas.
MF578_2003_10
Keywords: MF578; Economics; Crops; MF